Does large endometrioma per se increase AMH level?. Issue 4 (April 2021) - Younis, Johnny S.; Nelson, Scott M.
Abstract: Women with endometriosis, especially those with endometrioma, present a considerable challenge for ovarian reserve appraisal. This diagnostic difficulty arises from several fundamental questions inherently linked to patient management: the potential influence of endometrioma on ovarian reserve; the adverse effect of ovarian surgery on ovarian reserve; and the adequacy of the established ovarian reserve biomarkers, anti-Müllerian hormone and antral follicle count, to appraise ovarian reserve accurately in these women. Until recently, a key argument was that the development and growth of endometriomas is associated with a progressive damage to normal ovarian tissue, resulting in a concomitant reduction in serum AMH levels. Contrary to this widely accepted position; recent studies have reported that, in women with no previous history of ovarian surgery, AMH levels were increased in women with large endometriomas. These findings are surprising and, if replicated, would have substantial clinical implications. In this commentary, we would, however, urge caution before these reports lead to systematic changes in clinical practice, and recommend urgent replication as the finding linking large endometrioma to high serum AMH levels seems to be biologically implausible, and contradicts the existing extensive body of research.